Fictionality, Memory, and Epistemological Ecumenism in Chinua Achebe’s Arrow of God - Collins, Jason Emmett (Religion and the arts, 2025)
To the extent that the majority of documentation of the colonial encounter between Christianity and traditional “pagan” religion in West Africa is authored by Christian missionaries, an epistemological perspective that assumes the inherent superiority of Christianity dominates the historical record of this encounter. This article argues that, in his 1964 novel Arrow of God, Chinua Achebe leverages the discursive qualities unique to fiction to reimagine this historical encounter in an epistemologically ecumenical way. This reimagined perspective enables the reader to circumvent the challenges of the unbalanced historical record. At the same time, however, the very fictionality of the text continually signifies the dearth of similar archival evidence. In this way, Arrow of God is paradoxically both an act of remembering and an act of forgetting: remembering to the extent that it constructs a fascinating and plausible alternative to the biased historical record, and forgetting to the extent that the text’s necessarily imaginative quality continually memorializes the violence of the original erasure.